2004
DOI: 10.1063/1.1788853
|View full text |Cite
|
Sign up to set email alerts
|

Design of the collective Thomson scattering diagnostic for International Thermonuclear Experimental Reactor at the 60 GHz frequency range

Abstract: The physics feasibility study [H. Bindslev et al., ITER Report Contract No. EFDA 01.654, 2003, www.risoe.dk/euratom/CTS/ITER] concludes that the frequency option below the electron cyclotron resonance was the only system capable of meeting the International Thermonuclear Experimental Reactor (ITER) measurement requirements for the fusion alphas, with present or near term technology. This article presents the design of the collective Thomson scattering diagnostic for ITER at the 60 GHz range. The system is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…Indeed, previous feasibility studies [16] have found that such a diagnostic could fulfill the measurement requirements for ITER and that it could be combined with the CTS system foreseen to measure fast ion velocity distributions on ITER [17][18][19]. In preparation for proof-of-principle experiments the CTS receiver at TEXTOR was recently modified for measurements with frequency resolution better than 1 MHz [20] as would be required to demonstrate the ability to resolve cyclotron structure in CTS spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous feasibility studies [16] have found that such a diagnostic could fulfill the measurement requirements for ITER and that it could be combined with the CTS system foreseen to measure fast ion velocity distributions on ITER [17][18][19]. In preparation for proof-of-principle experiments the CTS receiver at TEXTOR was recently modified for measurements with frequency resolution better than 1 MHz [20] as would be required to demonstrate the ability to resolve cyclotron structure in CTS spectra.…”
Section: Introductionmentioning
confidence: 99%
“…At relatively large frequency shifts, here roughly beyond ±0.5 GHz, CTS measurements provide information about fast, nonthermal ion populations, e.g. from neutral beam heating [4][5][6][7][8][9][10][11][12][13][14] or from fusion reactions in future experiments with burning plasmas [15][16][17][18][19] . At lower frequency shifts, in the bulk ion region of the spectrum, CTS measurements provide information about thermal ion populations including properties such as the ion temperature and drift a) mspe@fysik.dtu.dk velocity (i.e.…”
mentioning
confidence: 99%
“…As in ITER, in the FTU sub-harmonic scenario the fundamental harmonic layer is located where the beam path is under vacuum. Nevertheless, it is worth noting that in FTU the 1 st harmonic layer is always close to the vacuum vessel wall, in front of the plasma-facing mirror surfaces, even using a high toroidal field such as 7.2 T. On the other side, according to the present design of the CTS system [21,22], the sub-harmonic operations -4 -…”
Section: High Field Scenario With B T T Tmentioning
confidence: 99%